Disparities in the incidence of acute myocardial infarction: long‐term trends from the Hunter region. Issue 5 (May 2017) - Davies, Allan J.; Naudin, Crystal; Al‐Omary, Mohammed; Khan, Arshad; Oldmeadow, Chris; Jones, Mark; Bastian, Bruce; Bhagwandeen, Rohan; Fletcher, Peter; Leitch, James; Boyle, Andrew
Abstract : Background: Trends in the incidence of acute myocardial infarction (AMI) provide important information for healthcare providers and can allow for accurate planning of future health needs and targeted interventions in areas with an excess burden of cardiovascular disease. Aim: To investigate the regional variations in AMI incidence in the Hunter region. Methods: Incident cases of AMI identified between 1996 and 2013 from the Hunter New England Health Cardiac and Stroke Outcomes Unit were prospectively collected for this study. We calculated crude and age‐adjusted incidence of AMI over an 18‐year period and explored differences in remoteness, age, sex and indigenous status. Results: During 1996–2013, a total of 15 480 cases of AMI were identified. There was a significantly higher incidence of AMI in patients from regional areas compared to patients from metropolitan areas. More importantly, while rates of AMI declined by 28% in metropolitan patients, they increased by 8% in regional patients. Males had higher rates of AMI throughout the study period than females, however there was trend over time towards a reduction in AMI incidence in males that was not seen in females. The age‐adjusted incidence of AMI for indigenous patients increased by 48% from 2007 to 2013, compared to a 23% decrease in non‐indigenous patients. Conclusion: Between 1996 and 2013 in the Hunter region, the adjusted incidence of AMI increased for regional patients compared to metropolitan patients with a trend towards a higher adjusted incidence of AMI in the indigenous population.